أثر المسؤولية الاجتماعية في تحقيق الرضاء الوظيفي للعاملين بالمؤسسات الاقتصادية: دراسة حالة شركة TPL بولاية الوادي - نسيب، أحمد; بلحاج، ياسين علي (جامعة زيان عاشور بالجلفة, 2021)
تهدف هذه الدراسة إلى معرفة أثر المسؤولية الاجتماعية على الرضاء الوظيفي للعاملين بشركة TPL بالوادي، استخدمت الدراسة المنهج الوصفي التحليلي، وتم الاعتماد على الاستبانة كأداة للحصول على البيانات، وسحبت عينة الدراسة بطريقة عشوائية، حيث قمنا بتوزيع 60 استمارة على العاملين بالشركة وتم استرجاع 40 استمارة، منها 07 غير صالحة للاستخدام. توصلت الدراسة لنتيجة مفادها تأكيد الفرضية الرئيسية التي نصت على وجود أثر ذو دلالة إحصائية للمسؤولية الاجتماعية على الرضاء الوظيفي للعاملين بالشركة محل الدراسة. ونقترح توصية لمسؤولي الشركة، محاولة خلق جو ملائم للعمل، وتحسين رواتب العاملين.
This study aims to know the impact of social responsibility on job satisfaction for employees of TPL company in the valley, the study used the descriptive analytical approach, and the questionnaire was relied on as a tool to obtain data, and the study sample was withdrawn in a random way, where we distributed 60 forms to the company’s employees and 40 questionnaires were retrieved. Of which 07 are not suitable for use. The study reached a conclusion that confirms the main hypothesis which stated that there is a statistically significant effect of social responsibility on the job satisfaction of the employees of the company under study. We suggest recommendations to company officials, trying to create a favorable atmosphere for work, and improve workers' salaries.
Keywords: المسؤولية الاجتماعية -- أداء العاملين -- المؤسسات الاقتصادية -- التنمية المستدامة -- الجزائر